Strategic air power in Desert Storm - Olsen, John Andreas, 1968- (Cass series--studies in air power ;, 2003)
"In response to the Iraqi invasion of Kuwait on 2 August 1990, a small group of air power advocates in the Pentagon, the so-called 'Checkmate' team led by Colonel John A. Warden III, proposed a strategic air campaign designed to drive the Iraqi army from Kuwait by a sustained effort against the major sources of Iraqi national power. Warden termed the proposal 'Instant Thunder' and although changes were made, the concept remained at the heart of what became the strategic air campaign in 'Operation Desert Storm'."--Jacket